2017
DOI: 10.1016/j.nima.2016.10.057
|View full text |Cite
|
Sign up to set email alerts
|

A feature point identification method for positron emission particle tracking with multiple tracers

Abstract: A novel detection algorithm for Positron Emission Particle Tracking (PEPT) with multiple tracers based on optical feature point identification (FPI) methods is presented. This new method, the FPI method, is compared to a previous multiple PEPT method via analyses of experimental and simulated data. The FPI method outperforms the older method in cases of large particle numbers and fine time resolution. Simulated data show the FPI method to be capable of identifying 100 particles at 0.5 mm average spatial error.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…If the nearby cells are of very similar activity, it is possible for the cells to be confused and switched during the tracking process. A brief discussion of this effect is found in [ 11 ]. If a sample cannot be prepared with well-separated cells, an application must be chosen such that occasional confusion of tracked cells will not detrimentally affect results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…If the nearby cells are of very similar activity, it is possible for the cells to be confused and switched during the tracking process. A brief discussion of this effect is found in [ 11 ]. If a sample cannot be prepared with well-separated cells, an application must be chosen such that occasional confusion of tracked cells will not detrimentally affect results.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the observation of trajectories stretching across many frames indicates that measured trajectories are not likely due to noise. Past work has shown that no false positive trajectories were observed when accepted trajectories were limited to those at least 20 time steps in length [ 11 ]. In this work, the shortest observed trajectory is 27 frames in length.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations